Resurgent Beaver Ponds in the Northeastern United States: Implications for Greenhouse Gas Emissions. Issue 6 (1st November 2014) - Lazar, Julia G.; Addy, Kelly; Welsh, Molly K.; Gold, Arthur J.; Groffman, Peter M.
Abstract : Beaver ponds, a wetland type of increasing density in the northeastern United States, vary spatially and temporally, creating high uncertainty in their impact to greenhouse gas (GHG) emissions. We used floating static gas chambers to assess diffusive fluxes of methane (CH4 ), carbon dioxide (CO2 ), and nitrous oxide (N2 O) from the air–water interface of three beaver ponds (0.05–8 ha) in Rhode Island from fall 2012 to summer 2013. Gas flux was based on linear changes of gas concentrations in chambers over 1 h. Our results show that these beaver ponds generated considerable CH4 and CO2 emissions. Methane flux (18–556 mg m −2 d −1 ) showed no significant seasonal differences, but the shallowest pond generated significantly higher CH4 flux than the other ponds. Carbon dioxide flux (0.5–22.0 g m −2 d −1 ) was not significantly different between sites, but it was significantly higher in the fall, possibly due to the degradation of fresh leaves. Nitrous oxide flux was low (0–2.4 mg m −2 d −1 ). Overall, CH4 and CO2 comprised most of the global warming potential, 61 and 38%, respectively. The shallowness of the beaver ponds may have limited the time needed for CH4 oxidation to CO2 before CH4 escaped to the atmosphere. Beaver dams also increase the aerial extent of hydric soils, which may transform riparian areas from upland GHG sinks to wetland GHG sources thereby changing the net global warming potential. Further studies tracking the pattern and conditions of beaver pond creation and abandonment will be essential to understanding their role as GHG sources.